Anterior Cruciate Ligament Injuries in Modern Football: A Review - Czerniakowski, Mikołaj; Sadok, Aleksandra; Kubas, Wojciech; Białek, Aleksandra; Karczewski, Jakub; Niemcewicz, Wojciech Jan; Ryń, Kamila; Koźlicka, Aleksandra; Klajda, Jakub; Gorczyca, Zuzanna (Quality in Sport, 2026)
Background: Anterior cruciate ligament (ACL) injuries are among the most severe and debilitating orthopedic traumas in modern football. The high-intensity nature of the sport, which demands frequent pivoting, rapid deceleration, and high-impact contact, significantly predisposes players to these injuries. Aim of the study: This comprehensive review aims to synthesize current epidemiological data, analyze in-depth injury mechanisms (including neurocognitive factors), evaluate surgical and non-operative management strategies, detail criteria-based return-to-sport (RTS) protocols, and review the efficacy of modern prevention strategies for ACL injuries in football players. Material and Methods: A comprehensive review of the literature was conducted utilizing 20 selected peer-reviewed articles, including national registries, meta-analyses, and systematic video analysis studies published between 2012 and 2025. Results: Recent literature indicates a substantial burden of ACL injuries in football, heavily influenced by the level of play, gender, and exposure type. Amateur players present a higher incidence rate (0.074/1000h) compared to professionals (0.058/1000h). Match-play exponentially increases the risk compared to training. Non-contact mechanisms account for over 55% of injuries, primarily occurring during defensive pressing and rapid deceleration. Emerging evidence highlights neurocognitive errors as significant contributors to non-contact ruptures. Female athletes face a 1.5 to 1.6-fold higher risk due to anatomical, hormonal, and biomechanical disparities. While surgical reconstruction (ACLR) remains the gold standard, returning to pre-injury performance is highly challenging. Only approximately 44-55% of athletes successfully return to competitive play, with fear of reinjury (kinesiophobia) acting as the primary barrier in 33% of failed cases. Furthermore, the risk of a secondary ACL injury reaches up to 30% in adolescent populations.